Factitious Disorder in Crohn's Disease: Recurrent Pancytopenia Caused by Surreptitious Ingestion of 6-Mercaptopurine - Allon Kahn; Erika S. Boroff; Kari A. Martin; Donald W. Northfelt; Russell I. Heigh (Case Reports in Gastroenterology, 2015)
Factitious disorder is a rare psychiatric illness characterized by the willful and deceptive induction of illness for the purpose of assuming the sick role. It presents a substantial diagnostic challenge, as patients often go to great lengths to conceal their deception. Accordingly, its presence in the full spectrum of gastrointestinal diseases is likely underappreciated. While factitious gastrointestinal bleeding, abdominal pain and diarrhea are relatively common, factitious non-gastrointestinal symptoms in the setting of gastrointestinal illness have been infrequently reported. We present the case of a patient with Crohn's disease with recurrent pancytopenia attributed to the surreptitious ingestion of 6-mercaptopurine. In patients with possible access to immunomodulatory drugs, a high suspicion for and early identification of factitious disorder may improve patient outcomes and avoid invasive and costly diagnostic evaluations.